GOOD GOVERNANCE GOVERNMENT AND GOVERNMENT - Fauza (Program Pascasarjana IAIN Langsa, 2019)
Good governance is increasingly popular when bad governance deals with KKN (corruption, collusion, and nepotism) actions. Good governance practices also require transparency in the overall governance process, while the formulation of the problem is how good governance is government and governance, Furthermore, the research method here is descriptive qualitative. The process begins with compiling the assumptions and rules of thought that will be used in the research. Information from research results It is more important in a very dynamic condition of community development, a better level of community life, which symbolizes